Thiopurine Methyltransferase Enzyme Activity Determination before Treatment of Inflammatory Bowel Disease with Azathioprine: Effect on Cost and Adverse Events. (1st May 2005) - Sayani, Farzana A; Prosser, Connie; Bailey, Robert J; Jacobs, Philip; Fedorak, Richard N
Abstract : BACKGROUND: Azathioprine (AZA), used to treat inflammatory bowel disease (IBD), is metabolized by thiopurine methyltransferase (TPMT). The accumulation of individual metabolites varies because humans display genetic polymorphism for TPMT expression. Deficiencies in TPMT result in accumulation of toxic metabolites, followed by neutropenia and hepatic inflammation. Concern over acute toxicity frequently leads to under dosing and frequent monitoring tests and visits. OBJECTIVE: To determine whether assessment of TPMT activity before the administration of AZA would predict acute toxicity and, thus, allow for reductions in health care costs related to biochemical screening for, and management of, AZA-induced adverse events. METHODS: Before AZA treatment, 29 patients with IBD were prospectivelyrandomized to one of two groups: group 1, in which no TPMT assay was performed, was started on AZA at 1 mg/kg/day and then titrated every two weeks to a target dose of 2.5 mg/kg/day; and group 2, in which TPMT assays were performed, was started on AZA at the target dose of 2.5 mg/kg/day. For both groups, complete blood count and liver enzymes were monitored weekly for six weeks and at monthly intervals thereafter. Additional tests and health care interventions were undertaken at the discretion of the attending physicians. RESULTS: Of the 29 patients in the study, 15 were randomly assigned to group 1 and 14 to group 2. Demographics and disease activity were similar for both groups. Mean follow-up time was 7.1 months (range 3.5 to 10.7 months). Eight patients from group 1 and six patients from group 2 withdrew as a result of AZA-induced adverse events. There was no correlation between the TPMT activity and the development of AZA-induced adverse events. The direct health care costs for group 1 (300.11 per patient) were lower than in group 2 (348.87 per patient). CONCLUSION: The prospective assessment of TPMT enzyme activity before initiating AZA therapy in IBD patients incurred additional cost and did not predict AZA-induced toxicity.